Advancing Geothermal Resource Assessment Using 3D Gravity Modeling: A Case Study from Kamojang, West Java - Agustin, Annisa Vidia; Early Nabila Dennanti; Meisha Nabilla; Nabilah Bintang Haryan; Ilham Dani (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
The research was conducted using the gravity method in the Kamojang geothermal manifestation area, West Java. Data was obtained through the Topex website which contains information on latitude, longitude, elevation, and FAA value. The purpose of this research is to determine the density value of subsurface constituent rocks to determine the location of reservoirs and heat sources in the research area. The corrections made are Bouger correction and Terrain correction obtained from the CBA map which is sliced as many as 5 incisions. Calculation of subsurface average mass density using the Parasnis method obtained a density of 2.5882 mGal. Spectrum analysis was performed to determine the regional-residual depth using the moving average method. The regional anomaly contour map shows a range of 15 - 135 mGal. The residual anomaly contour map shows a range of -26 to +28 mGal with more complex results. Modeling results using Grav3D with a mesh value of 500 show a density range of 1.6752 - 3.1712 gr/cm³ with an altitude of 600 - 2000 m and a thickness of 1400 m. Zones with high density values between 2.9219 - 3.1712 gr/cm³ are indicated as heat source areas with volcanic rocks such as lava to basalt igneous rocks. Medium density values in the range of 2.4232 - 2.6722 gr/cm³ are indicated as boundary zones which are interpreted as basement in the caprock of the study area with igneous rocks surrounding the boundary zone. The low density zone with a value of 1.6752 - 2.1732 gr/cm³ is indicated as a reservoir zone with sedimentary rocks composed of pyroclastic rocks and breccias.